The Effect of The Laps-Heuristic Learning Model on Students' Problem Solving Abilities - Kamid Kamid; Jefri Marzal; Syaiful Syaiful; Yellu Remalisa; Rina Kusuma Dewi (Journal of Educational Science and Technology (EST), 2021)
The purpose of this research is In 21st century learning students are required to be more active in learning than teachers, therefore this study aims to determine whether there is an influence between the LAPS-Heuristic learning model and the ability to solve problems. Methodology: Using quantitative descriptive. Where, the number of samples in this study were 436 students from SMP 11 Jambi City who used purposive sampling technique. Data were then analyzed with the help of SPSS 21 application to find descriptive statistics in the form of mean, min, max, and category as well as inferential statistics using simple regression. Finding: The results obtained in this study are dominant both in the ability of student problem solving and the effectiveness of the LAPS-Heuristic learning model in mathematics lessons. With this, it is strengthened by the existence of a relationship and influence between the LAPS-Heuristic learning model and the students' problem solving abilities seen from the sig value below 0.025, which is 0.019 and has a contribution of 70.3%.